Financial Performance on Company Value and Moderation of Corporate Social Responsibility: A Study of Mining Companies in Indonesia (Jurnal Manajemen Bisnis, 2026)
This study aims to determine and analyze the effect of financial performance, proxied by Return on Investment, Return on Assets, and Return on Equity, on company value, as well as to examine the role of Corporate Social Responsibility as a moderating variable in mining companies listed on the Indonesia Stock Exchange during the period 2020–2022. This study uses a quantitative approach with Moderated Regression Analysis (MRA). The data used is secondary data obtained from the annual financial reports of mining companies, accessed through the official website of the Indonesia Stock Exchange and the companies' official websites. The data collection technique uses the documentation method with purposive sampling to select samples based on criteria relevant to the research objectives. The results show that Return on Investment, Return on Assets, and Return on Equity have a positive and significant effect on company value. In addition, Corporate Social Responsibility was found to weaken the effect of Return on Investment on company value but to strengthen the effects of Return on Assets and Return on Equity on company value. This study provides practical contributions for companies to pay attention to the balance between financial performance and Corporate Social Responsibility implementation. The resulting managerial implications indicate that companies need to optimize financial performance and improve the quality of their CSR disclosures to maintain and increase their value in investors' eyes.